HIF-1α Alleviates High-Glucose-Induced Renal Tubular Cell Injury by Promoting Parkin/PINK1-Mediated Mitophagy - Yu, Lu; Wang, Yulin; Guo, Yan Hong; Wang, Liuwei; Yang, Zijun; Zhai, Zi Han; Tang, Lin (Frontiers in Medicine, 2022)
It is well-established that mitophagy leads to Diabetic Nephropathy (DN) and renal failure. Mitophagy mediated by Hypoxia-inducible factor-1α (HIF-1α) plays a beneficial role in many diseases. Nevertheless, the mechanisms underlying HIF-1α-mediated mitophagy in DN remain unclear. Our study aimed to define the role of HIF-1α mediated mitophagy in DN. The expression of HIF-1α was upregulated in HK-2 cells in a HG environment, and YC-1 (a specific inhibitor of HIF-1α) further exacerbated hypoxia-induced mitochondrial dysfunction. Conversely, the HIF-1α-mediated protective effect was strengthened by reactive oxygen species scavenger N-acetylcysteine (NAC). Moreover, HIF-1α stabilization could suppress ROS production, inflammation, EMT, and apoptosis via mitophagy in HK-2 cells in the HG environment. In summary, HIF-1α mediated mitophagy on HK-2 cells under HG conditions could alleviate DN, suggesting that it has huge prospects for DN treatment.